The Dissemination of Hijrah Doctrine on Social Media: A Study of Negotiation, Contestation, and Commodification of Religion - Fathurrosyid; Muthhar, Moh. Asy'ari; Kahar, Abd.; Mokhtar, Wan Khairul Aiman Wan (UIN Sunan Kalijaga Yogyakarta, 2024)
This research examines the process of disseminating the hijrah doctrine on social media, as well as the themes and motives attached to its dissemination. This study is a literature review using a virtual ethnography research model. Through a traveling theory approach, the study finds that: First, the dissemination of the hijrah doctrine on social media is predominantly carried out and shared by urban Muslims and millennial Muslims. Second, common themes used to disseminate the hijrah doctrine include Islamic clothing, early marriage propaganda, bank interest, and motivation for building an Islamic Caliphate state. These themes are disseminated through Hijrah Fest events, social media study groups, the narrative of agency socialization through artists and celebrities, and Islamist literature. This study argues that the dissemination of the hijrah doctrine on social media constitutes a form of religious commodification, with a larger agenda of promoting the movement to establish an Islamic Caliphate state.